An efficient S-band brillouin erbium fiber laser with additional EDFA - HARUN, S; CHENG, X; AHMAD, H (ELSEVIER SCI LTD, 2007)
A short wavelength band brillouin-erbium fiber laser (S-band BEFL) with enhanced characteristics is demonstrated using an additional erbium-doped fiber amplifier (EDFA) in the sub-loop of the laser system. Compared with the conventional BEFL without the additional EDFA, the enhanced BEFL has improved the number of channels as well as the flatness of the brillouin Stoke's peak power. By incorporating a double-pass EDFA, a stable output laser comb up to 8 channels was obtained at 1503 nm wavelength region with peak power variation for the first three Stokes is reduced from 30.9 to 5.4 dB. The incorporation of additional EDFA also increases the tuning range of the BEFL, which the maximum tuning range of 1.8 nm was obtained with the single-pass scheme. The S-band BEFL has constant spacing of 0.09 nm or 11 GHz, which has a potential application in dense wavelength division multiplexed system. (c) 2005 Elsevier Ltd. All rights reserved.